Recent advances in Takayasu's arteritis - DİRESKENELİ, RAFİ HANER (AVES, 2015)
Takayasu's arteritis (TAK) is a rare, chronic large-vessel vasculitis (LVV) that predominantly affects the aorta, its major branches, and the pulmonary arteries. Recent advances in the diagnosis, clinical course, disease assessment with biomarkers/imaging and new clinical tools, patient-reported outcomes, and new treatment options of TAK are discussed in this review. Conventional angiography, the gold standard method for initial diagnosis, appears to have been replaced with new imaging modalities such as magnetic resonance angiography (MRA) and 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) in recent years. MRA and FDG-PET are also promising for the assessment of disease activity. New tools for disease assessment such as Indian Takayasu's Arteritis Score 2010 (ITAS2010) and color Doppler ultrasound (CDUS) aim to better characterize and quantify disease activity

however, different imaging modalities in routine follow-up are not incorporated sufficiently in these approaches. Prognosis is possibly getting better, with lower mortality in recent years

however, it is difficult to assess the widely different vascular intervention rates among the clinical series. Leflunomide, tumor necrosis factor (TNF)-alpha antagonists, and tocilizumab are new options for patients resistant to conventional therapies. There is a clear need to develop a validated set of outcome measures for use in clinical trials of TAK. The Outcome Measures in Rheumatology (OMERACT) Vasculitis Working Group has taken on this task, finished a Delphi exercise with experts, and aims to develop a core set of outcomes for LVV in accordance with OMERACT Filter 2.0.
Keywords: Takayasu's arteritis; disease assessment; outcome; GIANT-CELL ARTERITIS; QUALITY-OF-LIFE; POSITRON-EMISSION-TOMOGRAPHY; COLOR-DOPPLER-ULTRASOUND; LARGE-VESSEL VASCULITIS; DISEASE-ACTIVITY; INITIAL VALIDATION; ITALIAN PATIENTS; F-18-FDG PET; TNF-ALPHA